2020
DOI: 10.1126/science.aay5356
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps target senescent vasculature for tissue remodeling in retinopathy

Abstract: In developed countries, the leading causes of blindness such as diabetic retinopathy are characterized by disorganized vasculature that can become fibrotic. Although many such pathological vessels often naturally regress and spare sight-threatening complications, the underlying mechanisms remain unknown. Here, we used orthogonal approaches in human patients with proliferative diabetic retinopathy and a mouse model of ischemic retinopathies to identify an unconventional role for neutrophils in vascular remodeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
141
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(150 citation statements)
references
References 85 publications
9
141
0
Order By: Relevance
“…In recent years, research on neutrophils in pathogen clearance, immunoregulation and disease pathology has made great progress [ 5 8 ]. Neutrophil extracellular traps (NETs), reticular chromatin structures, have become a new area of intense research focus in biology [ 9 12 ]. In an inflammatory state, NETs can cause tissue damage [ 10 , 11 , 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, research on neutrophils in pathogen clearance, immunoregulation and disease pathology has made great progress [ 5 8 ]. Neutrophil extracellular traps (NETs), reticular chromatin structures, have become a new area of intense research focus in biology [ 9 12 ]. In an inflammatory state, NETs can cause tissue damage [ 10 , 11 , 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to detrimental effects of NETs described above, a recent paper by Binet et al 39 provides evidence for a beneficial role of NETs in retinopathy. In a mouse model of ischaemic retinopathy, the researchers found that during vascular remodelling, senescent endothelial cells attracted neutrophils and triggered the extrusion of NETs by these cells.…”
Section: Nets and Other Structuresmentioning
confidence: 92%
“… NETs and vascular biology. Publications in 2020 found that NETs influence ( A ) ischaemic stroke, 35 ( B ) SMCs in atherosclerosis, 36 ( C ) circadian rhythm, 38 ( D ) senescent vascular cells, 39 ( E ) COVID-19 infection 40 and they can be inhibited using small polyanions 41 ( F ). Abbreviations: CCL-7, CC chemokine ligand 7; COVID-19, coronavirus disease 2019; CXCL2, C–X–C chemokine ligand 2; CXCR2, C–X–C chemokine receptor 2; ECs, endothelial cells; NETs, neutrophil extracellular traps; RBCs, red blood cells; SMCs, smooth muscle cells.…”
Section: Nets and Other Structuresmentioning
confidence: 99%
“…To assess the role of vascular endothelial cell senescence in explaining our CRISPR screens results, we re-analyzed our RNA-seq data using senescence and SASP curated gene sets 27 . This analysis did not yield significant enrichments for sgRNAs that target DHX38 or MAT2A ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…CRISPRa at the FURIN/FES, CCDC92/ZNF664 and CNNM2 loci activates a gene expression signature of senescence. ( A ) Gene-set enrichment analyses of the five RNA-seq experiments for four curated gene sets that capture senescence or the SASP 27 . The three CRISPRa experiments are highly significant for the senescence pathways.…”
Section: Resultsmentioning
confidence: 99%